Arbitrary 3D multi-body road vehicle modeling for vehicle-infrastructure interaction - Shiyi Mei; Colin Caprani; Daniel Cantero (Results in Engineering)
The impact of road vehicle loads on road infrastructure has become increasingly significant due to growing freight traffic in most countries. The traffic loads caused by heavy trucks depend on the vehicle types, configurations, and their dynamic interaction with the infrastructure. However, in most Vehicle-Infrastructure Interaction studies, custom axle models, such as configurations and axle groups, are often ignored, which could potentially amplify traffic loads. Applying conventional mathematical approaches to integrate these custom models into multi-body trucks with large degrees of freedom (DOFs) is generally intractable. Although powerful Multi-body Dynamics (MBD) and Finite Element (FE) software can model vehicles with complex configurations in great detail, their utilization is limited by high costs and long computation times. Thus, this paper proposes an approach based on Kane's method to systematically derive the equations of motion for general multi-body road vehicles with custom axle configurations and axle groups. By avoiding imposing traditional force and moment equilibrium, this approach can be easily applied to a Computer Algebra System (CAS): an open-source Python script based on CAS is provided for constructing symbolic matrices across various road vehicle configurations. The numerical results show that axle configurations and axle groups can influence the dynamic response of the road vehicle, particularly the contact force.